Status and trends of open access journals in the field of library and information science from 2003-2012 and 2013 - Singh, Ara Jenina C.; Obille, Kathleen Lourdes B. (Quezon City School of Library and Information Studies, University of the Philippines Diliman, 2014)
This study analyzed 150 Open Access Journals in the field of Library and Information Science from 2003-2012, and 2013, sourced from the Directory of Open Access Journals, L-Lists: List of Open Access Library and Information Science Journals, and Open Access Search Engine - Library and Information Science, together with the Journal of Philippine Librarianship.
Content analysis was employed to delve into various facets of Open Access Journals in the field. Specifically, the journals in this study were evaluated according their origin, language, start of publication, frequency of publication, consistency, provider, submissions, content, issue and article output.
This study analyzed 150 Open Access Journals in the field of Library and Information Science from 2003-2012, and 2013, sourced from the Directory of Open Access Journals, L-Lists: List of Open Access Library and Information Science Journals, and Open Access Search Engine- Library and Information Science, together with the Journal of Philippine Librarianship.
Content analysis was employed to delve into various facets of Open Access Journals in the field. Specifically, the journals in this study were evaluated according their origin, language, start of publication, frequency of publication, consistency, provider, submissions, content, issue and article output.
Principal findings show the consistency as well as an increase in the number of journals publishing via Open Access in the field of Library and Information Science. Furthermore : 1. Publication of the journals can be traced back to 40 countries from 6 continents and have been written in 19 different languages predominantly in English. 2. More than a third of the journals started their publication run prior to the specified timeframe of the study, with some of their archives dating back to the early 1900's. 3. Open Access Publications allow research materials to be released on a Rolling basis, making them available as soon as they're considered ready or complete. 4. Various institutions are behind the publications of the journals in this study - from Libraries, Universities, Associations and Organizations. Majority of which has been consistent in their publications, the contents of which catering primarily to their members. 5. Some of the journals utilize Open Journal Systems, a software made available for free online, designed to manage online journal publication. 6. Most of the journals accept article submissions although significant restrictions have been noted by the researcher. These include and are not limited to prohibition of articles that have already been published, Author Fees and language. 7. The increase in the production of issues and articles from 2003-2012, and even in 2013 is apparent. With a number of journals still expected to release publications for 2013, the current number of journals in publication as well as their issue and article output is highly competitive compared to previous years with the current number of research articles for 2013 being the highest recorded in that category as per annual figures.
Vita.
Thesis (Bachelor of Library and Information Science)
Keywords: Library services -- Periodicals; Information science -- Periodicals; Open access publishing